ANALISIS IMPLEMENTASI PSAK 72 DALAM PENGAKUAN PENDAPATAN PADA INDUSTRI REAL ESTATE: STUDI KOMPARATIF BSDE DAN PWON - Wila Triana; Rafli Faturrahman; Mawardahny Isyabilla; Yulita Triadiarti; Al Wahfi Suhada Sipahutar (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze and compare the implementation of PSAK 72 (Revenue from Contracts with Customers) in the real estate industry, focusing on PT Bumi Serpong Damai Tbk (BSDE) and PT Pakuwon Jati Tbk (PWON) for the 2025 fiscal year. The study employs a descriptive qualitative approach with a comparative method using content analysis of consolidated financial statements and notes to financial statements. The findings reveal that BSDE consistently recognizes revenue at a point in time, particularly upon the transfer of control when property units are handed over to customers. The main challenge lies in determining the existence of significant financing components arising from installment payment schemes. In contrast, PWON exhibits greater complexity due to the coexistence of revenue streams from property sales and rental activities, requiring separation between PSAK 72 and PSAK 73 implementation. Furthermore, both companies identify revenue recognition as a Key Audit Matter, highlighting the significant judgment required in assessing control transfer. This study concludes that although both entities apply the same accounting standard, differences in business models and asset portfolios lead to varying implementation complexities and managerial considerations. The findings contribute to a better understanding of revenue recognition practices in the property sector and provide insights for improving financial reporting transparency..